Modified feedback comb filter using harmonic distortion elimination for multi-channel demodulation - Bulaong, Grant Lewis Milan (Animo Repository, 2019)
A comb filter is a type of elementary filter in signal processing which is implemented by adding a delayed version of a signal to the original signal. Comb filters generally exist in two general forms, these are the feed-forward and the feedback. This paper proposes a modified comb filter system that allows optimization of performance in typical applications such as conjunction with Frequency-division multiplexing (FDM). The system uses harmonic distortion elimination for multi-channel demodulation. In addition, the filter system was also constructed in Direct Form (DF) and Cascaded Form (CF) to compare the results. Results show that passing frequencies that form a geometric sequence minimizes the harmonic distortion between the passed frequencies that allows reception of several channels at once while minimizing inter-channel interference during demodulation. Moreover, the researchers also found out that the frequency ratio must be precise and accurate as much as possible because the discrepancy between a desired frequency and a received frequency is non-uniform and increasing, in the case of following a geometric sequence. © 2019 IEEE.